SPATIAL-TEMPORAL EVALUATION OF THE MANGROVES OF THE CENTLA WETLANDS BIOSPHERE RESERVE, TABASCO - Pérez Sánchez, Eunice; Hernández Trejo, Humberto (Kuxulkab', 2024)
Mangroves are ecosystems of high ecological and economic value. In Mexico, 35 % of wetlands have been altered, which has prompted conservation measures such as accession to the Ramsar Convention and the creation of biosphere reserves. In Tabasco, the Pantanos de Centla Biosphere Reserve, a Ramsar site, has registered changes in mangrove cover. This study analyzes its evolution using Landsat images from 1986 and 2023. The results indicate a 51 % decrease in mangrove area. Although these ecosystems are resilient to adverse conditions, their degradation is still a reality. Since 1986, only 5,214 hectares of mangroves have persisted until 2023, with a 58 % probability of remaining in the future. The presence of mangroves in freshwater areas in the reserve underscores the importance of studying their structure to ensure their proper conservation.
Keywords: Mangroves; Centla; Change Trends